Doing public theology in the anthropocene towards life-creating theology - Meylahn, Johann-Albrecht (Verbum et ecclesia, 2015)
If one presumes that we are today living in the anthropocene, how does this challenge the doing of public theology? What is the calling of a public theologian in the anthropocene? To be able to answer these questions, this article shortly described the anthropocene and then sought to unpack a possible doing of theology in a particular local context, within the time of the anthropocene, creating (poiesis) a deconstructive space for possible resurrection life to emerge.